A long term follow-up study of the reconstruction of the oral cavity at a tertiary care center: An original research - Richa Kumari; Tanveer Karpe; Monika Gahlawat; Sachin Dev Singh; Abhishek Kumar; Vishal Kudagi (Wolters Kluwer Medknow Publications, 2023)
Introduction: In the subcontinent of India as well as for the other nations, the most usual cancer that affects the oral cavity the "squamous cell carcinoma". The main side effects of the intervention of the SCC are the large defect and disfigurement. This study sought to investigate the various interventions of the SCC in a designated cancer institute. Material and Methods: A retrospective clinical study of the records was done between 2000-2020 years. The operated cases were analysed for various patient demographics as well as the site of the lesion and number distributions. The change in the techniques and the preference flaps over the periods was noted, and the values were compared for every 5 years. Results: A1001 patients were treated between the intended periods. Though there were larger number of men, the variation was not significant. Common sites were floor of the mouth (FOM) and tongue. The common interventions were primary closure, soft tissue free flaps and bone flaps. The shift was seen towards the free flaps. Conclusion: The Free flaps were the common applications in the constructions. Bone free flaps overtook the other procedures that were commonly applied. The quality of life and the aesthetics are seen to be better with the free flaps.